Review of Methods for the Monitoring of Biomass and Vegetal Carbon in Tropical Forest Ecosystems - Fonseca, William (2017)
The quantification of vegetal biomass is the key to know the carbon that forest ecosystems store, and therefore, its capacity to mitigate climatic change. There is a variety of methods to estimate biomass, many with small variations, such as size and shape of sampling units, inclusion or not of any reservoir component (leaves, branches, roots, necromasses), minimum diameter inventoried, among others. The objective of the paper is to explain the most important aspects to be considered in the inventory of removals, based on the inventory design (statistical design, size and shape of the sampling units, components of the biomass to be evaluated). A second point deals with the determination of aerial biomass and roots, referring to the direct or destructive method, and indirect methods, especially to the use of mathematical models for their easy application and low cost; besides, some models for natural forest and plantations are noted. Reference is also made to the study of carbon in soils, biomass expansion factors, and how to determine carbon in biomass. We hope that these notes will facilitate the understanding of the topic and be a reference for the establishment of monitoring, reporting and verification schemes.